Estimation of population mean using auxiliary information in stratified sampling on successive occasion using ratio method - Singh, Satinder Pal; Bahl, Shashi (Annals of Agricultural Research, 2016)
In this paper tools of sampling theory have been developed and used for estimation of population mean. With the help of double sampling an effort has been made to improve the estimation in stratified sampling on successive occasion. The available information of the last occasion is used in improving the estimated mean in the current situation in stratified sampling. In case the population mean X of an auxiliary character X is known then a variety of estimators including ratio/regression and difference estimators are available for estimation of Y which is the mean of the character under study. Variance for ratio and double ratio estimators using ratio method has been derived. Also, an attempt has been made to study such an estimator under general sampling ways and even with specific sampling procedure.